Low temperature catalytic oxidation of volatile organic compounds: a review - Huang, Haibao; Xu, Ying; Feng, Qiuyu; Leung, Dennis Y. C (Catalysis science & technology, 2015)
Volatile organic compounds (VOCs) are toxic and recognized as one of the major contributors to air pollution. The development of efficient processes to reduce their emissions is highly required. Complete catalytic oxidation is a promising way to convert VOCs, especially with low concentration, into harmless CO 2 and water. This reaction is highly desirable to proceed at low temperature for the consideration of safety, energy savings, low cost and environmental friendliness. Great efforts have been devoted to develop efficient catalysts in order to reduce the temperature of catalytic oxidation of VOCs. The present review highlights recent important progress in the development of supported noble metal and metal oxide catalysts in this field. We examined several typical metals that are widely adopted as essential components for catalytic oxidation of VOCs and explored the effect of some important influencing factors such as the properties of metal and support, dispersion, particle size and morphology of metals. The specific mechanism that leads to superior catalytic activity towards low temperature VOC oxidation was discussed too. Volatile organic compounds (VOCs) are toxic and recognized as one of the major contributors to air pollution.